2021
DOI: 10.3892/ol.2021.12585
|View full text |Cite
|
Sign up to set email alerts
|

NCAPG upregulation mediated by four microRNAs combined with activation of the p53 signaling pathway is a predictor of poor prognosis in patients with breast cancer

Abstract: The role of non-SMC condensin I complex subunit G (NCAPG) in breast cancer remains unclear. The present study used online databases, reverse transcription-quantitative PCR, flow cytometry and western blotting to determine the expression levels, prognosis and potential molecular mechanisms underlying the role of NCAPG in breast cancer. The association between NCAPG expression and several different clinicopathological parameters in patients with breast cancer was determined, and the results revealed that NCAPG e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…First, we comprehensively analyzed the TCGA-glioma and GEO (GSE 10611 and 4290) datasets and detected a high expression of NCAPG in glioma; we then verified the results using the GEPIA online website. The functional enrichment of differentially expressed genes and NCAPG in gliomas predicted that NCAPG may be closely related to the cell cycle ( 32 ), p53 signaling pathway ( 33 ), and PI3K/ARK signaling pathway ( 34 ) in glioma, which is consistent with previous studies on NCAPG in tumors. Furthermore, we analyzed the relationship between the expression of NCAPG in glioma and the survival time of glioma patients, tumor classification, and IDH mutation using TCGA data.…”
Section: Discussionsupporting
confidence: 90%
“…First, we comprehensively analyzed the TCGA-glioma and GEO (GSE 10611 and 4290) datasets and detected a high expression of NCAPG in glioma; we then verified the results using the GEPIA online website. The functional enrichment of differentially expressed genes and NCAPG in gliomas predicted that NCAPG may be closely related to the cell cycle ( 32 ), p53 signaling pathway ( 33 ), and PI3K/ARK signaling pathway ( 34 ) in glioma, which is consistent with previous studies on NCAPG in tumors. Furthermore, we analyzed the relationship between the expression of NCAPG in glioma and the survival time of glioma patients, tumor classification, and IDH mutation using TCGA data.…”
Section: Discussionsupporting
confidence: 90%
“…Knockdown of NCAPG has been shown to regulate tumor proliferation, cell cycle and apoptosis through multiple signaling pathways [ 34 36 ]. Zhang et al [ 11 ] demonstrated that NCAPG regulates cardia adenocarcinoma progression both in vivo and in vitro via the PI3K/AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Non-SMC condensing complex subunit G (NCAPG) is a crucial component of the condensing complex, which binds to chromosomes at start of mitotic division and dissociates from them when mitotic division ends. Previous studies have reported that NCAPG is a promising therapeutic target across different tumor types, and it may be associated with development and progression of hepatocellular carcinoma (HCC) [25,26], esophageal squamous cell carcinoma (ESCC) [27], colorectal cancer (CRC) [28], breast cancer (BC) [29], prostate cancer (PCa) [30], kidney renal papillary cell carcinoma (KIRP) [31], endometrial cancer (EC) [32], bladder cancer (BLCA) [33], gastric cancer (GC) [34], glioblastoma (GBM) [35], and so on. And in the present study, we also find NCAPG was highly associated with the prognosis of ES; therefore, NCAPG may be a potential therapeutic target.…”
Section: Discussionmentioning
confidence: 99%